History and heritage of coastal protection in the southern tyrrhenian area - Maiolo, Mario; Carini, Manuela; Pantusa, Daniela; Capano, Gilda; Bonora, Marco Amos; Lo Feudo, Teresa; Sinopoli, Salvatore; Mel, Riccardo Alvise (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value=""1":2,"2":"The development of the sea economy (Blue Growth) represents an opportunity for worldwide coastal communities, which are increasing threatened by urban pressure, sea pollution, erosion processes and flooding events due to enhancing rate of relative sea level rise and storminess driven by climate change. These hazards pose several planning and management challenges to the stakeholders, often constrained in finding a compromise between flooding protection of the urban settlements, economic needs of the land and the health of the environment. Since historical and cultural stratification affected the landscape and the development of coastal urban areas, the Blue Growth involves the analysis of the history and heritage of the land, based on a scientific research capable to promote a sustainable economic development of the area. This manuscript focuses on the southern Tyrrhenian coast (Italy), first describing the historical and environmental features of the area and then focalizing on the impact of the anthropic interventions, with particular reference to the shoreline of Belvedere Marittimo (CS), where it is located the Marine Experimental Station of Capo Tirone, a strategic scientific hub that serves multiple research activities related to the marine environment, as the study of the hazards threating the environmental and cultural heritage, the development of new nautical and subsea technologies, and the dissemination of citizen-science into the Blue Growth framework."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">The development of the sea economy (Blue Growth) represents an opportunity for worldwide coastal communities, which are increasing threatened by urban pressure, sea pollution, erosion processes and flooding events due to enhancing rate of relative sea level rise and storminess driven by climate change. These hazards pose several planning and management challenges to the stakeholders, often constrained in finding a compromise between flooding protection of the urban settlements, economic needs of the land and the health of the environment. Since historical and cultural stratification affected the landscape and the development of coastal urban areas, the Blue Growth involves the analysis of the history and heritage of the land, based on a scientific research capable to promote a sustainable economic development of the area. This manuscript focuses on the southern Tyrrhenian coast (Italy), first describing the historical and environmental features of the area and then focalizing on the impact of the anthropic interventions, with particular reference to the shoreline of Belvedere Marittimo (CS), where it is located the Marine Experimental Station of Capo Tirone, a strategic scientific hub that serves multiple research activities related to the marine environment, as the study of the hazards threating the environmental and cultural heritage, the development of new nautical and subsea technologies, and the dissemination of citizen-science into the Blue Growth framework.